To reach the urinal one should descend the staircase in two goes of 8 or 80 steps (Revista Apotheke, 2017)
Departing from the consideration of Painting and the Readymade as concurrent traditions, therefore formative and constituent, in the territory of art, of its judgments and negotiations, the author looks at the condition of both practices in the context of contemporary art. Considering the reading of the pictorial production in the 1980s in Brazil on the part of artists, critics and historians, the author suggests that a critical revision of its postulates is still due.
Keywords: Painting and Readymade/Brazil; Brazil 1980s; Editing as strategy